2021
DOI: 10.1136/heartjnl-2020-318813
|View full text |Cite
|
Sign up to set email alerts
|

Improving detection and management of familial hypercholesterolaemia in Australian general practice

Abstract: ObjectiveFamilial hypercholesterolaemia (FH) is characterised by elevated low-density lipoprotein (LDL)-cholesterol and increased risk of cardiovascular disease. However, FH remains substantially underdiagnosed and undertreated. We employed a two-stage pragmatic approach to identify and manage patients with FH in primary healthcare.MethodsMedical records for 232 139 patients who attended 15 general practices at least once in the previous 2 years across five Australian States were first screened for potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The importance of intensive GP management of FH has been demonstrated in a study by Brett et al, which showed that implementing a pragmatic intervention plan by GPs, with the inclusion of statin/ ezetimibe medication±lifestyle advice, resulted in significant reduction in LDL-C levels. 24 While there is no clear explanation for the variation in LDL-C reduction in our study population, we hypothesise that this may be partly explained by the significant differences in baseline and treatment characteristics between individuals who attained the LDL-C treatment goal and those who did not. Perhaps older adults and those with higher LDL-C at baseline are more likely to be prescribed higher-intensity statins due to their perceived increased risk of CVD, which consequently results in better LDL-C treatment outcomes.…”
Section: Comparison With Previous Literaturementioning
confidence: 82%
“…The importance of intensive GP management of FH has been demonstrated in a study by Brett et al, which showed that implementing a pragmatic intervention plan by GPs, with the inclusion of statin/ ezetimibe medication±lifestyle advice, resulted in significant reduction in LDL-C levels. 24 While there is no clear explanation for the variation in LDL-C reduction in our study population, we hypothesise that this may be partly explained by the significant differences in baseline and treatment characteristics between individuals who attained the LDL-C treatment goal and those who did not. Perhaps older adults and those with higher LDL-C at baseline are more likely to be prescribed higher-intensity statins due to their perceived increased risk of CVD, which consequently results in better LDL-C treatment outcomes.…”
Section: Comparison With Previous Literaturementioning
confidence: 82%
“…The participating practices were involved in an Australia-wide National Health and Medical Research Council (NHMRC) partnership grant study (GNT 1142883) into 'Improving the detection and management of familial hypercholesterolaemia in Australian primary care'. 14,15 A total of 63 interviews with practice staff were undertaken. 16 Fifteen general practices across five Australian states were involved in the study, and all were participating in the planned education intervention after the baseline interviews were conducted.…”
Section: Study Sample and Settingmentioning
confidence: 99%
“…Brett et al in their study have shown that by simply using the current infrastructure of general practice, those affected by this condition can be successfully identified and treated. 2 The primary care electronic health record (EHR) is of course the key game changer, enabling swift identification of people in whom the diagnosis may be likely. Several variations to the approach of using EHR to identify FH cases have been described as shown in figure 1.…”
Section: Identifying Fh In Primary Care Using Current Infrastructurementioning
confidence: 99%
“…Several variations to the approach of using EHR to identify FH cases have been described as shown in figure 1. Options include systematically searching the records using established diagnostic criteria, such as Dutch Lipid Clinic Network (DLCN) criteria as used in the TARB-Ex tool 2 or novel case-finding tools, such as FAMCAT. 3 In parallel, electronic searches could create patientspecific computer reminders which alert the general practitioner (GP) opportunistically when a patient at increased risk of FH is seen.…”
Section: Identifying Fh In Primary Care Using Current Infrastructurementioning
confidence: 99%
See 1 more Smart Citation